Discovery and Design of Peptides as MMP9 Inhibitors through Structure-Based Molecular Docking for Targeted Mantle Cell Lymphoma Therapy - Yan, Wei; Yang, Ying; Yang, Wei; Wei, Minjie (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Enhanced expression and activation of metalloproteinase-9 (MMP9) are associated with Mantle Cell Lymphoma (MCL) progression, invasion and metastasis. Objective: To find a potential peptide inhibitor against MMP9, which, in turn, could inhibit MCL progression. Methods: We performed CCK8 assay, western blot, and transwell assays for RNAi activity. Molecular Operating Environment (MOE) software was applied for structural optimization as MMP9 and peptides were docked. We used gelatin zymography and confocal microscopy to confirm that the peptides can inhibit MMP9 activity. We applied CCK8 and transwell assay to evaluate cell proliferation and metastasis, and flow cytometry to evaluate cell cycle progression and apoptosis. Results: High MMP9 expression was observed in 49 of 88 samples (55.7%). Patients with high MMP9 expression were more likely to present with high stage (Stage 3-4, P=0.01), bone marrow invasion (P=0.033), and high-level LDH (P=0.000). High MMP9 expression was associated with significantly shorter overall survival (OS, HR=2.378, P=0.012) and progression-free survival (PFS, HR=2.068, P=0.03). Multivariate analysis identified high MMP9 expression (P= 0.027), high-risk mantle cell lymphoma international prognostic index (MIPI, HR=2.327, P=0.023), and no radiation therapy (P=0.035) as adverse prognostic factors. The silencing of MMP9 in Jeko-1 cells by RNAi suppressed cells migration and invasion in vitro (P<0.05). According to the docking results, peptide M3 bound deeply in the binding pocket of MMP9 and had interaction with the active-site Zn2+ ion in the catalytic domain. M3 was not only compatible with MMP9, but also inhibited its activity. M3 inhibited Jeko-1 cells proliferation, metastasis, and cell cycle progression, and promoted cell apoptosis rate (P<0.05). Conclusion: We designed M3 through structure-based molecular docking, which can specifically bind to MMP9 and inhibit the activity of MMP9. M3 could be a potential antagonist in the treatment of MCL with MMP9 overexpression.
Keywords: inhibitors